Improving paediatric and neonatal care in rural district hospitals in the highlands of Papua New Guinea: a quality improvement approach - Sa’avu, Martin (Maney Publishing, 2014)
BACKGROUND: In developing countries such as Papua New Guinea (PNG), district hospitals play a vital role in clinical care, training health-care workers, implementing immunization and other public health programmes and providing necessary data on disease burdens and outcomes. Pneumonia and neonatal conditions are a major cause of child admission and death in hospitals throughout PNG. Oxygen therapy is an essential component of the management of pneumonia and neonatal conditions, but facilities for oxygen and care of the sick newborn are often inadequate, especially in district hospitals. Improving this area may be a vehicle for improving overall quality of care. METHOD: A qualitative study of five rural district hospitals in the highlands provinces of Papua New Guinea was undertaken. A structured survey instrument was used by a paediatrician and a biomedical technician to assess the quality of paediatric care, the case-mix and outcomes, resources for delivery of good-quality care for children with pneumonia and neonatal illnesses, existing oxygen systems and equipment, drugs and consumables, infection-control facilities and the reliability of the electricity supply to each hospital. A floor plan was drawn up for the installation of the oxygen concentrators and a plan for improving care of sick neonates, and a process of addressing other priorities was begun. RESULTS: In remote parts of PNG, many district hospitals are run by under-resourced non-government organizations. Most hospitals had general wards in which both adults and children were managed together. Paediatric case-loads ranged between 232 and 840 patients per year with overall case-fatality rates (CFR) of 3–6% and up to 15% among sick neonates. Pneumonia accounts for 28–37% of admissions with a CFR of up to 8%. There were no supervisory visits by paediatricians, and little or no continuing professional development of staff. Essential drugs were mostly available, but basic equipment for the care of sick neonates was often absent or incomplete. Infection control measures were inadequate in most hospitals. Cylinders were the major source of oxygen for the district hospitals, and logistical problems and large indirect costs meant that oxygen was under-utilized. There were multiple electricity interruptions, but hospitals had back-up generators to enable the use of oxygen concentrators. After 6 months in each of the five hospitals, high-dependency care areas were planned, oxygen concentrators installed, staff trained in their use, and a plan was set out for improving neonatal care. INTERPRETATION: If MGD-4 targets for child health are to be met, reducing neonatal mortality and deaths from pneumonia will have to include better quality services in district hospitals. Establishing better oxygen supplies with a systems approach can be a vehicle for addressing other areas of quality and safety in district hospitals.